(3efJNH GdCMcGes - (3CHh YHO Gddg eMeO Hf YHO Gddg Hf YjSi GdeQj, GHf CHj Refjf,J (B399 (3g` s
(3ChdgG (B:s
(3hHYO aEf gPG cJGH LeYJ ajg hGfJNHfG MSGfkG LjGOkG s
(3BNQgG (B:s
(3bGd GHf MHjH eKd bhd eWQa PcQg Yf GHf GdbGSe s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B227s
(3eUOQ GbJfGA GdCUd (B:s
(3CSchQjGd s
Keywords: (3CUhd Gdabgs